Recommendations and practices for the screening of depression and anxiety in acute coronary syndrome: a scoping review protocol. (July 2018) - Franzon, Julie; Haren, Matthew T.; Kourbelis, Constance; Marin, Tania; Newman, Peter; Jones, Martin; Muir-Cochrane, Eimear; Clark, Robyn A.
Abstract : Objective: The objective of this scoping review is to identify and map current recommendations and practices for the screening of depression and anxiety in acute coronary syndrome patients in the acute care setting. Specifically, the review questions are: What are the screening tools recommended for use in depression and anxiety screening in acute coronary syndrome patients? How is the screening for depression and anxiety in acute coronary syndrome patients integrated into cardiac models of care? What is the evidence practice gap in the screening for depression and anxiety in acute coronary syndrome patients in the acute care setting?